2014
DOI: 10.3892/ol.2014.1952
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin-induced apoptosis in human colon cancer LoVo cells

Abstract: A number of scientific studies have revealed that laminarin has antitumor effects. Therefore, the aim of the present study was to investigate the apoptosis of LoVo cells and the underlying mechanisms induced by laminarin. LoVo cells were treated with various concentrations of laminarin and fluorescence-inverted microscopy was used to observe the morphology of LoVo cells treated with laminarin. In addition, western blotting was performed to analyze the expression levels of death receptor (DR)4, DR5, TNF-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…In another human colon cell line HT-29, laminarin was proved to induce apoptosis of cancer cells by regulating the insulin-like growth fator-IR (IGF-1R) signaling pathway (107). In the same cell line LOVO, laminarin was demonstrated by another research group to increase apoptosis of cancer cells by activating the death receptor (DR) signaling pathway (108).…”
Section: Polysaccharidementioning
confidence: 99%
“…In another human colon cell line HT-29, laminarin was proved to induce apoptosis of cancer cells by regulating the insulin-like growth fator-IR (IGF-1R) signaling pathway (107). In the same cell line LOVO, laminarin was demonstrated by another research group to increase apoptosis of cancer cells by activating the death receptor (DR) signaling pathway (108).…”
Section: Polysaccharidementioning
confidence: 99%
“…The regulatory mechanisms of laminarin in tumors are complex and have been suggested to be associated with ErbB2 phosphorylation, mitochondria, and the death receptor pathway in CC cells. 9,10,21 In this study, the expression of a prognostic marker of HCC, SMP-30, was detected. We found that the treatment with laminarin significantly increased the expression of SMP-30 in Bel-7404 and HepG2 cells but not in LO2 cells, compared with the expression in the control cells.…”
Section: Discussionmentioning
confidence: 84%
“…Laminarin was found to increase the release of hydrogen peroxide, calcium, nitric oxide, monocyte chemotactic protein-1, vascular endothelial growth factor, leukemia inhibitory factor, and granulocyte-colony stimulating factor in RAW 264.7 cells (Lee et al, 2012). It is known to induce apoptosis in human colon cancer cells by multiple pathways (Ji and Ji, 2014). It demonstrated protective effect against cisplatin-induced ototoxicity (Han et al, 2016).…”
Section: Activities Of Sulfated Polysaccharides and Exopolysaccharidementioning
confidence: 99%